ChatGPT and Education Transformation A SWOT Analysis Towards an Innovative and Ethics-Based Curriculum in the Digital Era - Cahyani (Generate Digital Publishing, 2025)
Objective: This study aims to provide a systematic and evidence-based understanding of the strengths, weaknesses, opportunities, and threats (SWOT) of integrating ChatGPT, an artificial intelligence (AI)-based chatbot, in an educational context. Research Design & Methods This study used a descriptive qualitative approach with a SWOT analysis framework to evaluate the strategic aspects of using ChatGPT in the teaching and learning process. Data were collected through a literature review and observation of the practice of using AI in education. Findings: The analysis shows that ChatGPT has strengths in generating logical and relevant responses, providing real-time feedback, and supporting personalized learning. However, there are weaknesses such as limited depth of understanding, potential bias, and inability to accurately assess cultural context and academic relevance. Opportunities include facilitating access to information and simplifying teaching activities, while threats include the risk of plagiarism, academic ethical challenges, and perpetuating discrimination in the learning process. Implications & Recommendations: This study recommends developing a holistic approach that integrates AI into instructional design while emphasizing the importance of strengthening critical thinking skills and digital literacy. In addition, clear ethical guidelines are needed to ensure fair and responsible use of ChatGPT. Contribution & Value Added: This study contributes by offering a SWOT-based evaluative framework to understand the impact of ChatGPT in education and provides direction for further research related to optimizing AI-based learning and developing ethical policies in academic writing.